ANALYZE THE MARKET POTENTIAL OF WIZORLD’S PRODUCT IN SIVAKASI - Dr.S.Tephillah Vasantham,; Dr.J.Pràveen Paul,; Mr.N.Senthil Kumaran, (EPRA International Journal of Research and Development (IJRD), 2022)
Marketing is the manner on doing someone actions as makes more beautiful on the manufacture then services so much makes a vast affect the audiences through a amazing messaging. Through content, advertising objectives in accordance with entrust a high value worth because of prospects then customers including the long-term purpose for strengthening company loyalty then demonstrating manufacture value as nicely so makes ultimately increasing sales. Marketing is the manner on working human beings more fascinated in the direction of the company’s manufacture then services. This desire show up via a number steps kind of want research, evaluation yet understanding the target customer yet theirs interests. Marketing is mated between whole elements regarding enterprise as incldes sales then advertising, product improvement or dole methods.